Government effectiveness, economic growth and the socio-political role of the middle class in Bangladesh - Md. Rubel Mia; Jill L. Tao; Chad Anderson (Institute of Computer Science (IOCS), 2022)
The objectives of the study are to develop an understanding of major changes such as the effectiveness of government, economic growth, religion and the socio-political role of the middle class people that have taken place in the society and politics of Bangladesh of the last few years. Apart from that this study also intends to analyze the crisis of the democratic system in Bangladesh and the widespread influence of religion on politician of the society. In addition to that, the context of the developments of economic growth in Bangladesh is significant over the last few decades, which has helped in the emergence and development of a new middle class in the country. In the past, it has been said theoretically and in the light of the experience of different countries that economic growth and development of the middle class simultaneously strengthen democracy and reduce the political appeal of religion in the society and politics. All in all, this study attempted to presents some hypotheses on the particular issues of Bangladesh.